(untitled) (Journal of Engineering, 2020)
Experimental tests were carried to control lost circulation in the Khabaz oil field using different types of LCMs including Nano-materials. A closed-loop circulation system was built to simulate the process of lost circulation into formations. Two dolomite plugs were used from different depths of the formation of Azkand in Khabaz oil field. The experimentations were carried out to study the effect of different types of LCMs, cross-linked copolymer (FLOSORB CE 300 S), SiO2 NP, and Fe2O3 NP, on mud volume losses as a function of time. The rheological measurements of the nanoparticles-reference mud system showed that both of the SiO2 NP and Fe2O3 NP worked best at 1.2 g/l. and the closed-loop circulation system showed that SiO2 NP cured losses by 48.3% and 37.5% for core plugs 5C1 and 1C2 respectively which is better than Fe2O3 NP loss curing which was 37.9% and 31.3% for core plugs 5C1 and 1C2 respectively. On the other hand, FLOSORB CE 300 S- Fe2O3 NP-reference mud systems cured losses up to 69% with 0.25g/l FLOSORB CE 300 S and 79.3% with 0.5 g/l FLOSORB CE 300 S which is better than the FLOSORB CE 300 S- SiO2 NP-reference mud systems results.